Job Satisfaction, Workplace Spirituality, and Organizational Citizenship Behavior and Their Impact on Employee Performance at PT Bukit Makmur Mandiri Utama - Syahrial, Ryan Alif; Tanuwijaya, Justine (Jurnal Manajemen, 2023)
This study aimed to determine the effect of job satisfaction, workplace spirituality, and organizational citizenship behaviar for emplooye perfomance. This research uses a quantitative approach method, and the sample is taken using purpose sampling technique with the population being employees from all jobsite of companies in PT Bukit Makmur Mandiri Utama (BUMA). Data collection was done online using Google Forms and resulted in 233 responses that could be used. The results showed that four from three hypotheses were supported. The results obtained from this study are expected to benefit company management in analysze and mapping the level of job satisfaction, workplace spirituality, and organizational citizenship behaviour for emplooye performance.